Fathers' encounter of support from paediatric diabetes teams; the tension between general recommendations and personal experience. (28th November 2012) - Boman, Åse; Povlsen, Lene; Dahlborg‐Lyckhage, Elisabeth; Hanas, Ragnar; Borup, Ina
Abstract The purpose of this grounded theory study was to explore and discuss how fathers involved in caring for a child with type 1 diabetes experienced support from Swedish paediatric diabetes teams (PDTs) in everyday life with their child. Eleven fathers of children with type 1 diabetes, living in Sweden and scoring high on involvement on the Parental Responsibility Questionnaire, participated. Data were collected from January 2011 to August 2011, initially through online focus group discussions in which 6 of 19 invited fathers participated. Due to high attrition, the data collection continued in eight individual interviews. A semi‐structured interview guide was used, and the fathers were asked to share experiences of their PDT's support in everyday life with their child. A simultaneous and constant comparison approach to data collection and analysis allowed the core category to emerge: the tension between general recommendations and personal experience. This core category illuminates how the fathers experienced tension between managing their unique everyday life with their child and balancing this to meet their PDT's expectations with regard to blood glucose levels. The core category was supported by two categories: the tension between the fathers'and their PDT's knowledge, whereby fathers reported discrepancies between their PDT's medical knowledge and their own unique knowledge of their child; and the tension between the fathers'and their PDT's goals, whereby the fathers identified differences between the familys' and their PDT's goals. As a dimension of the core category, fathers felt trust or distrust in their PDT. We conclude that to achieve high‐quality support for children with diabetes and to enhance their health and well‐being, involved fathers' knowledge of their unique family situation needs to be integrated into the diabetes treatment.